Occasional photographic records of butterflies (Lepidoptera, Papilionoidea) in Cambodia: 3, Pursat, Siem Reap, Preah Vihear and Stung Treng Provinces in western, north-western and northern Cambodia - Oleg E. Kosterin (Acta Biologica Sibirica, 2020)
Abstract The butterfly (Papilionoidea) fauna of Cambodia is very rich but too insufficiently studied. Results are presented of occasional photographic records of butterflies (Lepidoptera, Papilionoidea) made in 2016–2019 (some also in 2006) along with studies on the Odonata fauna in 67 localities of western and northern provinces of Cambodia: Pursat, Siem Reap, Preah Vihear and Stung Treng. This paper completes the two previous communications of this series devoted to the south-western and eastern provinces of this country. In total, 162 identified and 13 provisionally identified species are listed; 22 species (Miletus ancon, Arhopala agrata, A. alesia, A. allata, A. ammonides, A. atrax, A. aurelia, A. moolaiana, A. silhetensis, Drupadia theda, Anthene licates, Prosotas aluta, Danaus chrysippus, Cirrochroa surya, Doleschallia bisaltide, Athyma ranga, Euthalia recta, Burara oedipodea, Hasora chromus, Pseudocoladenia dan, Koruthalaios sindu, Parnara ganga) are for the first time reported in literature for Cambodia. These and some problematic species are illustrated. Some misidentifications in the two first communications of the series are made; due to reidentification Arhopala camdana and Borbo cinnara are for the first time reported for Cambodia in literature.